2022
DOI: 10.3390/life12081158
|View full text |Cite
|
Sign up to set email alerts
|

Rare Causes of Acute Coronary Syndrome: Carbon Monoxide Poisoning

Abstract: Acute coronary syndrome (ACS) is a spectrum of clinical and paraclinical disorders arising from an imbalance of oxygen demand and supply to the myocardium. The most common cause is atherosclerosis; however, other rare causes such as carbon monoxide (CO) poisoning should be considered. Through tissue hypoxia and direct cell injury, CO poisoning can lead to a broad spectrum of cardiac disorders, especially ACS. Materials and Methods. We have conducted a retrospective study in the Toxicology Department of Saint S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A study by Dragelyte et al stated that carbon monoxide poisoning can lead to angina and myocardial injury in patients of a younger age irrespective of existing cardiovascular comorbidities [24]. At any extent of carbon monoxide poisoning level, myocardial injury can ensue as a transient, reversible, or permanent presentation [25]. In a study by Satran et al, 37% of carbon monoxide poisoning patients were found to have myocardial injury, as determined via ECG or biomarkers (troponin I level of > 0.7 ng/mL or CK-MB mass > 5.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dragelyte et al stated that carbon monoxide poisoning can lead to angina and myocardial injury in patients of a younger age irrespective of existing cardiovascular comorbidities [24]. At any extent of carbon monoxide poisoning level, myocardial injury can ensue as a transient, reversible, or permanent presentation [25]. In a study by Satran et al, 37% of carbon monoxide poisoning patients were found to have myocardial injury, as determined via ECG or biomarkers (troponin I level of > 0.7 ng/mL or CK-MB mass > 5.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular complications caused by CO poisoning have mostly been reported as left ventricular dysfunction, arrhythmias, and pulmonary edema, but it can also induce a coronary spasm and intracoronary thrombosis, leading to acute coronary syndrome even in healthy patients and in ones with non-critical atherosclerotic plaques. Some patients may have ST depressions or T wave inversions [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is sometimes difficult, as typical chest pain can be missed in the early presentation [ 17 ] or it can be completely absent [ 18 ]. Haliga et al found that dysrhythmia was more common with mild CO poisoning (17.2%) compared to levels of 7.7% and 8.7% in cases of moderate and severe poisoning, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%